(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article examines the forms, methods, and principles of tax control from a theoretical and analytical perspective. Tax control is considered an essential component of the public financial management system and an important mechanism for ensuring compliance with tax legislation. The study analyzes the main forms of tax control, including desk (cameral) audits, field tax inspections, tax monitoring, and tax audits. In addition, the methods applied in tax control such as documentary verification, analytical evaluation, comparative analysis, and risk-based assessment discussed. The article also highlights the fundamental principles guiding tax control activities, including legality, transparency, systematic implementation, and efficiency. The findings indicate that effective tax control contributes significantly to improving tax compliance, strengthening fiscal discipline, and ensuring stable budget revenues. Furthermore, the study emphasizes the growing role of digital technologies, automated information systems, and risk-oriented approaches in enhancing the efficiency of tax administration and control mechanisms. The research concludes that the modernization of tax control practices is essential for ensuring sustainable economic development and improving the effectiveness of fiscal policy.